2022
DOI: 10.1093/jxb/erac004
|View full text |Cite
|
Sign up to set email alerts
|

When rain collides with plants—patterns and forces of drop impact and how leaves respond to them

Abstract: Raindrop impact on leaves is a common event which is of relevance for numerous processes, including the dispersal of pathogens and propagules, leaf wax erosion, gas exchange, leaf water absorption, and interception and storage of rainwater by canopies. The process of drop impact is complex and its outcome depends on many influential factors. The wettability of plants has been recognized as an important parameter which is itself complex and difficult to determine for leaf surfaces. Other important parameters in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 87 publications
0
20
0
Order By: Relevance
“…For example, it was found in some studies that trichomes could promote water condensation on the leaf surface and increase FWU (Konrad et al, 2015), whereas other studies found that trichomes are water‐repellent which is often recognized as one of the trichomes' protection functions (Brewer & Smith, 1997; Konrad et al, 2021). This is because the interactions of trichomes with water are influenced by a variety of factors, including not only the special chemical and structural properties described above, but also other factors such as trichome density, leaf properties, water form (e.g., minute or macro droplets), the pattern in which the water interacts with the trichomes (e.g., contact angle), environmental conditions and physiological situations (Roth‐Nebelsick et al, 2022).…”
Section: The Role Of Trichomes In Water Absorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it was found in some studies that trichomes could promote water condensation on the leaf surface and increase FWU (Konrad et al, 2015), whereas other studies found that trichomes are water‐repellent which is often recognized as one of the trichomes' protection functions (Brewer & Smith, 1997; Konrad et al, 2021). This is because the interactions of trichomes with water are influenced by a variety of factors, including not only the special chemical and structural properties described above, but also other factors such as trichome density, leaf properties, water form (e.g., minute or macro droplets), the pattern in which the water interacts with the trichomes (e.g., contact angle), environmental conditions and physiological situations (Roth‐Nebelsick et al, 2022).…”
Section: The Role Of Trichomes In Water Absorptionmentioning
confidence: 99%
“…Indeed, not all plant trichomes can absorb water. For example, the egg‐beater‐like trichomes of the floating fern ( Salvinia molesta ) are highly water‐repellent and can keep its leaves largely free from water even when the leaf is immersed in water or during rainfall events (Konrad et al, 2021; Roth‐Nebelsick et al, 2022). This again indicates that the structure and function of trichomes can be highly variable and likely evolved to assist plants to cope with a range of biotic and abiotic stress factors.…”
Section: Future Research Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results were compared to those of the nanoscale strips exhibiting excellent hydrophobicity. In nature, the impact pressure of raindrops could reach 20–40 atm. , When the role of wind was included, the pressure would even rise to 198 atm . Therefore, the structures and free-energy profiles of metastable and transition states under different pressures were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The biomechanics of plant tissue under wind dynamics such as leaf fluttering has been investigated using different mechanical models ( Gonzalez-Rodriguez et al., 2016 ; De Langre, 2019 ; Geitmann et al., 2019 ; Jackson et al., 2021 ; Langer et al., 2022 ; Lauderbaugh and Holder, 2022 ; Roth-Nebelsick et al., 2022 ). Some of them consider the effect of foreign bodies like insects on leaf mechanics ( Whitney and Federle, 2013 ).…”
Section: Introductionmentioning
confidence: 99%